Synergistic Effect of Cation Composition Engineering of Hybrid Cs1−xFAxPbBr3 Nanocrystals for Self‐Healing Electronics Application. Issue 9 (5th January 2023) - Liang, Fang‐Cheng; Jhuang, Fu‐Cheng; Fang, Yu‐Han; Benas, Jean‐Sebastien; Chen, Wei‐Cheng; Yan, Zhen‐Li; Lin, Wei‐Chun; Su, Chun‐Jen; Sato, Yuki; Chiba, Takayuki; Kido, Junji; Kuo, Chi‐Ching
Abstract: Mixed‐cation hybrid perovskite nanocrystal (HPNC) with high crystallinity, color purity, and tunable optical bandgap offers a practical pathway toward next‐generation displays. Herein, a two‐step modified hot‐injection combined with cation compositional engineering and surface treatment to synthesize high‐purity cesium/formamidinium lead bromide HPNCs(Cs1‐ x FA x PbBr3 ) is presented. The optimized Cs0.5 FA0.5 PbBr3 light‐emitting devices (LEDs) exhibit uniform luminescence of 3500 cd m −2 and a prominent current efficiency of 21.5 cd A −1 . As a proof of concept, a self‐healing polymer (SHP) integrated with white LED backlight and laser prototypes exhibited 4 h autonomous self‐healing through the synergistic effect of weak reversible imine bonds and stronger H‐bonds. First, the SHP‐HPNCs‐initial and SHP‐HPNCs‐cut possess high long‐term stability and dramatically suppressed lead leakage as low as 0.6 ppm along with a low leakage rate of 1.11 × 10 −5 cm 2 and 3.36 × 10 −5 cm 2 even over 6 months in water. Second, the Cs0.5 FA0.5 PbBr3 HPNCs and SHP‐induced shattered–repaired perovskite glass substrate show the lowest lasing threshold values of 1.24 and 8.58 µJ cm −2, respectively. This work provides an integrative and in‐depth approach to exploiting SHP with intrinsic and entropic self‐healing capabilities combined with HPNCs to develop robust and reliable soft‐electronic backlight and laser applications. Abstract : Novel post‐synthesis cesium/formamidinium (Cs/FA) mixed‐cation perovskite nanocrystals possess high structural and optoelectronic properties for integration in self‐healing polymer composites. Entropic‐driven self‐healing not only enhances white backlight display performance, but also sustains the working performance of a shattered–repaired glass substrate laser, thereby representing potentially major advances in optoelectronics and photonics applications.